Analisis Manajemen Strategi Dalam Menghadapi Persaingan Bisnis : Studi Kasus UMKM Cireng Tijang Kota Serang - Annisa Nurfadilla; Mita Rosita; Nanda Trisna Dewi; Riki Gana Suyatna (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
This research was conducted at UMKM Cireng Tijang, the purpose of this study was to find out the Management Strategy in Facing Business Competition. The research used is a descriptive qualitative approach, namely an explanatory data analysis and information related to the theories that will be analyzed in qualitative research and provides conclusions from this research. The subject of this research is UMKM Cireng Tijang. Data collection techniques used were library research, observation, interviews and documentation, the data sources used were primary data and secondary data, and data analysis consisted of inductive techniques, deductive techniques and conclusion drawing. The research results obtained regarding Strategic Management Analysis in Facing Business Competition using a Cost Advantage Strategy, where a cost advantage strategy can be carried out by providing high quality products to customers or innovating the products offered to optimally retain customers.